2011
DOI: 10.1016/j.ijsu.2010.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The role of ultrasound scan in the diagnosis of occult inguinal hernias

Abstract: Ultrasound scan alone in diagnosing groin hernias is not effective when correlated with operative findings. However in conjunction with clinical judgment it is a useful tool in diagnosing occult inguinal groin hernias and aiding in further management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 8 publications
3
39
0
Order By: Relevance
“…Light et al reported that despite showing a hernia in an ultrasound in 116 examined patients, it was not observed during the surgery in 31 cases. In addition, hernia is sometimes observed during a surgery despite not having been observed during both clinical and ultrasound examinations [14]. Hence, the following question arises: what type of preoperative pain reported by a patient should first and foremost make a physician suspect a hernia with a lack of other obvious symptoms in the inguinal region?…”
Section: Discussionmentioning
confidence: 99%
“…Light et al reported that despite showing a hernia in an ultrasound in 116 examined patients, it was not observed during the surgery in 31 cases. In addition, hernia is sometimes observed during a surgery despite not having been observed during both clinical and ultrasound examinations [14]. Hence, the following question arises: what type of preoperative pain reported by a patient should first and foremost make a physician suspect a hernia with a lack of other obvious symptoms in the inguinal region?…”
Section: Discussionmentioning
confidence: 99%
“…All the studies included in this review were prospective except 1 retrospective study 12 . That study retrospectively reviewed a patient cohort that had suspected occult groin hernias and had proceeded to sonography and subsequent management, either surgical or conservative.…”
Section: Study Design Characteristicsmentioning
confidence: 99%
“…Three studies looked exclusively at patients with palpable inguinal hernias 13 15 . Two studies investigated patients with groin pain but no palpable inguinal hernias 12 , 16 . The remaining 4 studies looked at a combination of these patient groups 17 20 .…”
Section: Study Design Characteristicsmentioning
confidence: 99%
“…Diagnosis by sonography is reported to obtain sensitivities as high as 94% to 100%. 18,19 The inguinal canal should be imaged with the patient supine, before and while the patient performs the Valsalva maneuver. If no hernia is visualized, images should be taken while the patient is standing.…”
Section: Discussion Herniasmentioning
confidence: 99%